Classes of non-resonating-node lowpass prototype networks suitable for realisation as evanescent-mode waveguide bandpass filters - Fathelbab, Wael M (IET microwaves, antennas & propagation, 2018)
This work presents four classes of lowpass prototype networks comprising non-resonating-nodes (NRNs) realising generalised elliptic function transfer characteristics. Each class of networks can realise a maximum of (N − 2) finite-frequency transmission zeros where N is the total number of the resonators in the network. The distinct feature pertinent to the proposed classes of networks is that they can be sub-classed into two types: type I networks have positive frequency-invariant elements (FIEs) located at the NRNs, and type II networks have negative FIEs located at the NRNs. type I networks are particularly suitable for the realisation as evanescent-mode waveguide (EMW) bandpass filters which is the main subject of this work, whereas type II networks could be realised as waveguide bandpass filters operating above the cut-off of the guide. Numerical examples of the four classes of the proposed networks are presented. The proposed circuit concepts are validated through the realisation of two classes of filters in EMW technology created utilising computer simulation technology (CST) microwave studio. The electrical performance of the CST filter structures and their circuit counterparts are in close agreement.